Self-Medication in the Pandemic Era: Factors to Consider Based on the Theory of Health Belief Model - Sudhewa, Sang Putu Bagus Vidya Dharma; Widowati, I Gusti Ayu Rai; Empuadji, Putu Prayascitadevi; Suryaningsih, Ni Putu Aryati; Sutema, Ida Ayu Manik Partha (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2023)
One of the factors leading people to seek treatment during the Covid-19 outbreak is a lack of access to healthcare services. Based on the Health Belief Model Theory, the purpose of this study is to investigate community self-medication and its determinants. An observational study was conducted in Bali Province, Indonesia. The study included adults who bought the medicine at a pharmacy without a prescription. Validated questionnaires were distributed in a drugstore in Gianyar Regency from January to February 2022. The variables were 4 (four) factors of health belief, demographics, socioeconomic position, and COVID-19 history. The analysis was descriptive, with 400 respondents out of 420 recruited (95.2% response rate). The affecting factors were identified as health confidence, cost reduction, and health condition prevention. There were 69.3% (n=277) of Covid-19 suspects with symptoms of fever, cough, runny nose, and headache. Indicators of socioeconomic status were also discovered. In terms of perceived susceptibilities, 54.0% (n=216) respondents reported mild symptoms; 260 (65.0%) respondents reported distance to the pharmacy as a perceived benefit; drug dose was also reported as a perceived barrier (n=229;57.25%), and 365 (91.3%) respondents reported perceived severities to prevent worsening of health conditions. The community's self-medication is still a concern. Behavior modification necessitates tactics that rely on health beliefs and target persons of lower socioeconomic levels. We believe that pharmacists should provide drug information to customers for self-medication to be effective.